Application of the thermal energy storage concept to novel epoxy–short carbon fiber composites. Issue 21 (23rd January 2019) - Dorigato, A.; Fredi, G.; Pegoretti, A.
ABSTRACT: For the first time, multifunctional epoxy–short carbon fiber reinforced composites suitable for thermal energy storage technology were developed. Paraffin microcapsules (MC) and short carbon fibers (CFs) were added at different relative amounts to an epoxy matrix, and the microstructural and thermomechanical properties of the resulting materials were investigated. Scanning electron microscopy images of the composites showed a uniform distribution of the capsules within the matrix, with a rather good interfacial adhesion, while the increase in the polymer viscosity at elevated CF and MC amounts caused an increase in the void content. Differential scanning calorimetry tests revealed that melting enthalpy values (up to 60 J/g) can be obtained at high MC concentrations. The mixing and thermal curing of the composites did not lead to breakage of the capsules and to the consequent leakage of the paraffin out of the epoxy matrix. The thermal stability of the prepared composites is not negatively affected by the MC addition, and the temperatures at which the thermal degradation process begins were far above the curing or service temperature of the composites. Flexural and impact tests highlighted that the presence of MC reduces the mechanical properties of the samples, while CF positively contributes to retaining the original stiffness and mechanical resistance. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47434. Abstract :